Measuring the costs of short-termism - Davies, Richard; Haldane, Andrew G.; Nielsen, Mette; Pezzini, Silvia (Journal of Financial Stability, 2014)
A potential cost of modern capital markets is short-termism, with agents in the financial intermediation chain weighing near-term outcomes too heavily at the expense of longer-term opportunities and thus forgoing valuable investment projects and potential output. This paper sets out an analytical framework and empirical estimates of the potential costs of short-termism arising from distortions to the cost of capital and investment intentions.